2018
DOI: 10.1002/ps.5145
|View full text |Cite
|
Sign up to set email alerts
|

Potential investment tradeoff between offspring production and functional recovery promoted by larval cannibalism inCoccinella septempunctata(Coleoptera: coccinellidae)

Abstract: Leg-regenerated ladybugs caused by cannibalism may make an investment tradeoff between egg fecundity and functional recovery. Thus, larval cannibalism potentially improves the offspring production of the biological control agent in complex environments. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…However, regeneration also requires a trade-off between functional recovery and other developmental traits. Previous studies on limb regeneration in ladybird beetles (Abdelwahab et al, 2018;Michaud, Nedved, et al, 2020;Wang et al, 2015;Wu, Ma, et al, 2019;Yang et al, 2016) have reported a few developmental and reproductive costs. Till now, regeneration studies on C. sexmaculata have reported the influence of limb regeneration on the adult reproductive fitness (Saxena et al, 2016) and the effect of thermal conditioning during limb regeneration (Rai et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, regeneration also requires a trade-off between functional recovery and other developmental traits. Previous studies on limb regeneration in ladybird beetles (Abdelwahab et al, 2018;Michaud, Nedved, et al, 2020;Wang et al, 2015;Wu, Ma, et al, 2019;Yang et al, 2016) have reported a few developmental and reproductive costs. Till now, regeneration studies on C. sexmaculata have reported the influence of limb regeneration on the adult reproductive fitness (Saxena et al, 2016) and the effect of thermal conditioning during limb regeneration (Rai et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests against the use of contralateral legs as an internal control in regeneration studies. The smaller leg segments could affect the overall morphology of the adult leg, which in turn may alter other predatory behaviours, such as prey consumption, searching rate and handling time in adults (Wu, Ma, et al., 2019). Individuals with reduced forelegs might choose smaller prey, which has been observed in many crustaceans, arachnids and insects (Brueseke et al., 2001; Juanes & Smith, 1995; Wu, Ma, et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations